The practice of evidence in the hearings of constitutional guarantees in Ecuador - López Álvarez, Reinaldo Patricio (2025)
This article reviews the importance of jurisdictional actions as a way to protect fundamental rights in Ecuador, emphasizing the analysis of the practice of evidence in hearings of constitutional guarantees, in the field of protection action.  The main objective is to establish the admission, assessment of the evidence and its implications for the safeguarding of human rights. The methodology used is qualitative, by virtue of which a normative, jurisprudential and doctrinal analysis is carried out in order to understand the way in which jurisdictional actions intersect with the guarantee of fundamental rights. The results found show that despite having legislation that has advanced, there are great misgivings in the implementation of the test, which affects the solution of the cases and the impartiality of the decisions.